2013
DOI: 10.1590/0037-8682-0145-2013
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a rapid diagnostic test for the detection of visceral leishmaniasis in a large urban setting

Abstract: Introduction: Rapid diagnostic tests (RDTs) may improve the early detection of visceral leishmaniasis (VL), but their real-world performance requires additional study. Therefore, we evaluated the performance of an rK39-based RDT (Kalazar Detect TM ) for the detection of VL in an endemic, large urban area. Methods: Data were collected from a registry of rK39 RDT performed at 11 emergency care units in Belo Horizonte, Brazil, and from a national database of reportable communicable diseases of the Sistema de Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
(38 reference statements)
0
9
1
2
Order By: Relevance
“…There is no consensus in the literature as to the amphotericin dose for the treatment of VL in renal transplant recipients. Previous studies used lower doses (20 mg divided in four doses and 1 mg/kg/day for 10 days) and shorter periods of time and observed a high cure rate of VL patients [ 40 , 41 ]. This study investigated cases of VL after renal transplantation diagnosed between 1989 and 2013.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus in the literature as to the amphotericin dose for the treatment of VL in renal transplant recipients. Previous studies used lower doses (20 mg divided in four doses and 1 mg/kg/day for 10 days) and shorter periods of time and observed a high cure rate of VL patients [ 40 , 41 ]. This study investigated cases of VL after renal transplantation diagnosed between 1989 and 2013.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, conducted in Brazil, Guimarães- Carvalho et al (2003) showed that the sensitivity and specificity of rK39-ICT were 90% and 100%, respectively [50]. However, in more recent studies, also conducted in Brazil, rK39-ICT showed high specificity but low sensitivity [51,52]. These studies, evaluating the performance of rK39-ICT in same or different regions, highlight the variability and inconsistency in the performance of rK39.…”
Section: Elisa Testmentioning
confidence: 99%
“…The sensitivity of recombinant K39 protein (rK39) rapid tests, such as IT-LEISH® (Bio-Rad Laboratories, Hercules, CA, USA, and DiaMed, Cressier, Switzerland) and Kalazar Detect® (InBios International, Seattle, WA, USA) ranged from 72.4 to 87.59% and specificity, from 99.6 to 100% in blood or serum [163, 164]. HIV infection decreased sensitivity to 60% [163], but performance was not affected by malnutrition [165]. The reproducibility of immunochromatographic strip rK39 was very low (kappa 0.14) in one study in Brazil [166].…”
Section: Resultsmentioning
confidence: 99%